SIMULTANEOUS VISCOUS-INVISCID COUPLING VIA TRANSPIRATION - Yiu, K; Giles, M (1995)
In viscous-inviscid coupling analysis, the direct coupling technique and the inverse coupling technique are commonly adopted. However, stability and convergence of the algorithms derived are usually very unsatisfactory. Here, by using the transpiration technique to simulate the effect of the displacement thickness, a new simultaneous coupling method is derived. The integral boundary layer equations and the full potential equation are chosen to be the viscous-inviscid coupled system. After discretization, the Newton-Raphson technique is proposed to solve the coupled nonlinear system. Several numerical results a re used to demonstrate the accuracy and efficiency of the proposed method. Copyright © 1995 Academic Press. All rights reserved.